(untitled) (Journal of human and social sciences, 2022)
This 367-page book is a rare study of Arab-Islamic heritage, documenting treasures, gifts, banquets, and diplomatic exchanges from the pre-Islamic and Islamic periods. It highlights two main themes: the material culture of caliphs, rulers, and notable figures, and the diplomatic ties between Arab and foreign kingdoms. The ten chapters cover gifts, famous banquets, feasts, ceremonies, rare treasures, inherited possessions, estates of caliphs’ families, spoils of war, hidden wealth, and pre-Islamic expenditures. An appendix illustrates Fatimid-era artifacts from the Islamic Art Museum in